Nanoemulsion: An Emerging Novel Technology for Improving the Bioavailability of Drugs - null Preeti; Sharda Sambhakar; Rohit Malik; Saurabh Bhatia; Ahmed Al Harrasi; Chanchal Rani; Renu Saharan; Suresh Kumar; null Geeta; Renu Sehrawat (Scientifica)
The pharmaceutical sector has made considerable strides recently, emphasizing improving drug delivery methods to increase the bioavailability of various drugs. When used as a medication delivery method, nanoemulsions have multiple benefits. Their small droplet size, which is generally between 20 and 200 nanometers, creates a significant interfacial area for drug dissolution, improving the solubility and bioavailability of drugs that are weakly water-soluble. Additionally, nanoemulsions are a flexible platform for drug administration across various therapeutic areas since they can encapsulate hydrophilic and hydrophobic medicines. Nanoemulsion can be formulated in multiple dosage forms, for example, gels, creams, foams, aerosols, and sprays by using low-cost standard operative processes and also be taken orally, topically, topically, intravenously, intrapulmonary, intranasally, and intraocularly. The article explores nanoemulsion formulation and production methods, emphasizing the role of surfactants and cosurfactants in creating stable formulations. In order to customize nanoemulsions to particular medication delivery requirements, the choice of components and production techniques is crucial in assuring the stability and efficacy of the finished product. Nanoemulsions are a cutting-edge technology with a lot of potential for improving medication bioavailability in a variety of therapeutic contexts. They are a useful tool in the creation of innovative pharmaceutical formulations due to their capacity to enhance drug solubility, stability, and delivery. Nanoemulsions are positioned to play a crucial role in boosting medication delivery and enhancing patient outcomes as this field of study continues to advance.